Thermal computations for electronics : conductive, radiative, and convective air cooling - Ellison, Gordon N. (Boca Raton, FL : CRC Press, Taylor & Francis Group, 2020)
"The flavor and organization of the first edition has been retained whereby the reader is guided through the analysis process for systems and then components. Important new material has been added regarding altitude effects on forced and buoyancy driven airflow and heat transfer. The first twenty percent of the book is devoted to the prediction of airflow and well-mixed air temperatures in systems, circuit board channels, and heat sinks, followed by convective (PCB-mounted components included), radiative, and conductive heat transfer and the resultant temperatures in electronic equipment. Detailed application examples illustrate a variety of problems"--
OCLC-licensed vendor bibliographic record.
Keywords: Electronic apparatus and appliances -- Thermal properties -- Mathematical models; Electronic apparatus and appliances -- Cooling -- Mathematics; TECHNOLOGY / Construction / Heating, Ventilation & Air Conditioning; TECHNOLOGY / Electricity; TECHNOLOGY / Electronics / General